LGBTIQ-fobia, una mirada a los delitos de lesa humanidad desde la diversidad sexual (Tema Central) - Chávez Rivera, Brayan Alexander (2024)
Discrimination and gender-based violence directed against the LGBTIQ+ population have been structured over the years in a heteronormative, sexist, patriarchal and religious society, thus causing serious violations of human rights related to factors in the commission of crimes such as homicide, feminicide and torture; Something characteristic of the commission of these acts is the systematicity and the factor of sexual and gender diversity by which they are carried out, in order to adapt a conservative thought implemented in society, causing different forms of discrimination, hate speech and intersectionality. that affect the full development and guarantee of a dignified life for the LGBTIQ+ population. Due to the anxiety generated in the LGBTIQ+ population, and added to this the historical feature of this systematic violence, it is necessary and interesting to address the perspective of crimes against humanity from an analysis of sexual diversity as an indisputable factor that gender and sexual diversities must have an intervention and application of the classifications contemplated in the Rome Statute, seeking that these international instruments fully adapt to present social realities and that have caused concern and obligations in the international community for a full guarantee of rights and social equality for the LGBTIQ+ population.